APLIKASI PENJUALAN GROSIR BERBASIS WEB PADA CV. SARWODADI - Edy Sahputro, slamet Cahyo; Aznar Abdillah, Muhamad; Niko Fernanda, Edgar (STMIK Komputama Majenang, 2021)
This research is motivated by the owner of a wholesale pen trading business, so far CV. SARWODADI is still doing promotions and sales manually, so the range of promotions and sales is still limited and cannot be extended to several areas which causes the products produced to be less well known by the wider community. Troubleshooting solutions in CV. SARWODADI, namely by implementing a website-based sales application, so that it is expected to increase sales and marketing of CV. SARWODADI. The goal achieved is as a promotional media on the CV. SARWODADI and make it easier for consumers to see and buy products without having to go to the store. The research method used is the interview method, namely by asking questions directly to the owner of the UD. Irma Jaya Pen about how the flow of sales transactions, purchases, availability of goods, and the reporting process in CV. SARWODADI. Library Method by reading books and understanding materials related to Web-Based Wholesale Sales Applications on CV. SARWODADI is to learn the manual system that is running on CV. the SARWODADI. The result to be achieved is that it is hoped that the Web-Based Wholesale Sales Application can overcome the problems that exist in the old system so that it is able to meet all system needs.